Experimental Verification of the Elastic Response in a Numeric Model of a Composite Propeller Blade with Bend Twist Deformation - Sondre Østli Rokvam (MDPI AG, 2021)
Adaptive composite propeller blades showing bend twist behaviour have received increasing interest from hydrodynamic and structural engineers. When exposed to periodic loading conditions, such propellers can be designed to have higher energy efficiency and emit less noise and vibration than conventional propellers. This work describes a method to produce an adaptive composite propeller blade and how a point load experiment can verify the predicted elastic response in the blade. A 600 mm-long hollow full-size blade was built and statically tested in the laboratory. Finite element modelling predicted a pitch angle change under operational load variable loads of 0.55°, a geometric change that notably compensates for the load cases. In the laboratory experiment, the blade was loaded at two points with increasing magnitude. The elastic response was measured with digital image correlation and strain gauges. Model predictions and experimental measurements showed the same deformation patterns, and the twist angle agreed within 0.01 degrees, demonstrating that such propellers can be successfully built and modelled by finite element analysis.